knit-knotters - Hay, Sam; Tran, Turine (New York, NY Branches/Scholastic Inc, 2016)
Stella discovers that her new glasses are magic, allowing her to see the knit-knotters--night sprites that are flitting around town tyeing knots in children's hair so they need haircuts--and when a conversation with one of them, Trixie, reveals the reason, Stella comes up with a plan to deal with the mischievous fairies
English stories
2
Keywords: Eyeglasses -- Juvenile fiction; Fairies -- Juvenile fiction